Synergistic complement lysis by monoclonal antibodies to the human leukocyte common antigen requires both the classical and alternative pathways. - Bindon, C; Hale, G; Hughes-Jones, N; Gorick, B; Waldmann, H (1987)
In a previous study we isolated a series of rat monoclonal antibodies to the human leukocyte common (LC) antigen and demonstrated that synergistic complement lysis was possible between IgG2b antibodies which recognised different epitopes. In this report we have examined the mechanisms that were involved in synergistic lysis. We found that the number of C1q binding sites increased from 30,000 to 40,000/cell using a single antibody to 90,000/cell when two IgG2b antibodies to different epitopes were used together. The affinity of C1q binding also increased approx. 3-fold for the synergistic pair, and there was a similar increase in the rate of C1 activation. Combinations of an IgG2b with IgG1 or IgG2a gave much smaller increases in the amount of C1q bound and in the rate of C1 activation. Despite the large number of C1q molecules bound with the optimal synergistic pair and the increased rate of C1 activation, lysis was inefficient in serum depleted of Factor D, suggesting a requirement for the alternative pathway. This is the first demonstration of the need for the alternative pathway in complement lysis by monoclonal antibodies.